Effect of caffeine on the neuromuscular system - potential as an ergogenic aid - Tarnopolsky, M. A. (Applied Physiology, Nutrition, and Metabolism, 2008)
The ergogenic effect of caffeine on endurance exercise performance is multifactorial; however, there is evidence for an effect on both the central nervous system and the excitation-contraction coupling of skeletal muscle. The increase in exercise performance seen following intracerebroventrical caffeine injection in rats provides strong evidence for a central ergogenic effect. The central ergogenic effect is not likely related to the ability of caffeine to promote wakefulness, but could be due to an increase in the pain and effort perception threshold. There is no evidence that caffeine alters peripheral nerve conduction velocity or neuromuscular transmission, and 1 study showed that motor unit synchronization was not altered by caffeine. Studies have also shown that caffeine can have a direct effect on skeletal muscle that could be ergogenic. For example, patients with high cervical spinal cord lesions showed improvements in stimulated contractile force during cycling, in spite of the fact that they have no peripheral pain input and no sympathetic nervous system response. Two studies have found a potentiation of force production during submaximal stimulation intensities, and 1 found that the M-wave amplitude was not altered by caffeine. Together, these studies suggest that caffeine can enhance contractile force during submaximal contractions by potentiating calcium release from the ryanodine receptor, not by altering sarcoplasmic excitability. Furthermore, the potentiation of force during submaximal electrical stimulation is identical in habitual and nonhabitual caffeine consumers. In summary, the ergogenic effects of caffeine during endurance activity are mediated partly by enhanced contractile force and partly by a reduction in perceived exertion, possibly though a blunting of effort and (or) pain.